A house for the nuclear family: the case of Ghana. Issue 3 (2nd September 2018) - Adu-Gyamfi, Albert
ABSTRACT: The motivation to achieve homeownership varies according to cultural and national contexts. However, research on homeownership needs of the nuclear family has mainly focused on developed countries with little known in developing countries. Using in-depth interviews, this paper explores how the needs of the nuclear family influence the attainment of homeownership in the Ghanaian city of Kumasi. Findings suggest that individuals attain homeownership foremost for the reason of accommodating their expanding families. Even though this reason for homeownership is pervasive across various geographical and cultural contexts, the peculiar Ghanaian situation is how individuals concurrently bear the cost of attaining a house and meet their needs. It is obvious that the advantages that homeownership provides act as an incentive for its attainment. One such is the ability to nurture children to achieve positive social, physical and cognitive traits. In addition, homeownership ensures privacy, security, wealth and income benefits to homeowners. These benefits are especially important to the surviving family of a deceased homeowner.